Modern English Language Didactics: Aspects of Dialectics and Analisis - E. V. Yakovleva; R. V. Agadzhanyan (Vestnik MGIMO-Universiteta)
The article offers a review of the most important trends in language didactics as revealed by the consistent development of academic thought in the field over the period of 20th-21st centuries. The aforesaid process has laid foundations for modern didactic practices in foreign language teaching, as it addresses media and competence approaches to cross-cultural understanding of functional characteristics, highlighting the new generation didactic materials.